2010
DOI: 10.1071/py09032
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous men's support groups and social and emotional wellbeing: a meta-synthesis of the evidence

Abstract: Indigenous men's support groups are designed to empower men to take greater control and responsibility for their health and wellbeing. They provide health education sessions, counselling, men's health clinics, diversionary programs for men facing criminal charges, cultural activities, drug- and alcohol-free social events, and advocacy for resources. Despite there being approximately 100 such groups across Australia, there is a dearth of literature on their strategies and outcomes. This paper is based on partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 9 publications
0
42
0
Order By: Relevance
“…Similar to other initiatives for indigenous individuals with SUDs (Chenhall, 2007;Stevenson, 1999;Vick et al, 1998), the women's group of this study draws on Aboriginal culture and storytelling to bring about positive change. However, few programs that are embedded in a socio-cultural approach have been systematically evaluated (McCalman et al, 2010). Our study is unique in its analysis of current and optimal approaches to facilitate such an approach.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other initiatives for indigenous individuals with SUDs (Chenhall, 2007;Stevenson, 1999;Vick et al, 1998), the women's group of this study draws on Aboriginal culture and storytelling to bring about positive change. However, few programs that are embedded in a socio-cultural approach have been systematically evaluated (McCalman et al, 2010). Our study is unique in its analysis of current and optimal approaches to facilitate such an approach.…”
Section: Discussionmentioning
confidence: 99%
“…Aboriginal and Torres Strait Islander men's groups across Australia (McCalman et al 2010). The vision of Aboriginal and Torres Strait Islander men has been to take responsibility themselves to improve the status of men's health and play their rightful role as leaders, fathers, uncles, husbands and grandfathers (Briscoe 2000).…”
Section: Context and Literaturementioning
confidence: 99%
“…for more than a third of respondents. The importance of social relations among the men's group members is mentioned in a study by McCalman et al (2010). "Help in experiencing one's own faith in God" (c) was important for a fifth of respondents and (d) "Broadening of horizons" for 17% of them.…”
Section: Examples Of Answersmentioning
confidence: 99%
“…Their research was conducted using the method of Participatory Action Research that is based on the presumption that chosen members of the group will carry out the research (in this case: two). This study demonstrated the utility of men's groups, which teach their members respect, responsibility and increased wellbeing for themselves and their families (McCalman et al, 2010). Golding, Foley, Brown, and Harvey (2007) investigated senior men's groups in Australia.…”
Section: Men's Groups Researchmentioning
confidence: 99%
See 1 more Smart Citation